Sex-Based Differences in Functional Brain Activity During Working Memory in Survivors of Pediatric Acute Lymphoblastic Leukemia. Issue 2 (11th April 2022) - Gandy, Kellen; Scoggins, Matthew A; Phillips, Nicholas; van der Plas, Ellen; Fellah, Slim; Jacola, Lisa M; Pui, Ching-Hon; Hudson, Melissa M; Reddick, Wilburn E; Sitaram, Ranganatha; Krull, Kevin R
Abstract: Background: Long-term survivors of pediatric acute lymphoblastic leukemia are at elevated risk for neurocognitive deficits and corresponding brain dysfunction. This study examined sex-based differences in functional neuroimaging outcomes in acute lymphoblastic leukemia survivors treated with chemotherapy alone. Methods: Functional magnetic resonance imaging (fMRI) and neurocognitive testing were obtained in 123 survivors (46% male; median [min-max] age = 14.2 years [8.3-26.5 years]; time since diagnosis = 7.7 years [5.1-12.5 years]) treated on the St. Jude Total XV treatment protocol. Participants performed the n-back working memory task in a 3 T scanner. Functional neuroimaging data were processed (realigned, slice time corrected, normalized, smoothed) and analyzed using statistical parametric mapping with contrasts for 1-back and 2-back conditions, which reflect varying degrees of working memory and task load. Group-level fMRI contrasts were stratified by sex and adjusted for age and methotrexate exposure. Statistical tests were 2-sided ( P  < .05 statistical significance threshold). Results: Relative to males, female survivors exhibited less activation (ie, reduced blood oxygen dependent–level signals) in the right parietal operculum, supramarginal gyrus and inferior occipital gyrus, and bilateral superior frontal medial gyrus during increased working memory load (family-wise error–corrected P  = .004 to .008, adjusting for age and methotrexate dose). Female survivors were slower to correctly respond to the 2-back condition than males ( P  < .05), though there were no differences in overall accuracy. Performance accuracy was negatively correlated with fMRI activity in female survivors (Pearson's r  = −0.39 to −0.29, P  = .001 to .02), but not in males. Conclusions: These results suggest the working memory network is more impaired in female survivors than male survivors, which may contribute to ongoing functional deficits.